Sistem Informasi Inventaris Toko berbasis Web untuk UMKM Penyewaan Kostum - Ridwansyah Ridwansyah; Dary Mochamad Rifqie; Nuridayanti Nuridayanti (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Inventory recording is critical for business players, not only for giant corporations but also for micro, small, and medium enterprise (MSMEs). A thorough record of entering and exiting items can reduce errors, streamline work procedures, and make future investment decisions easier. However, due to limited human resources in information technology, MSMEs may continue to keep records manually. Store N, a costume rental MSME, also encountered a similar issue. Business owners need help keeping track of the rotation of costumes, especially at certain events. This research aims to create a web-based shop inventory information system based on the waterfall model to assist store N in running its business. Purchases, rentals, returns, and the state of costumes are all recorded centrally in a database. The research results found that this system functions properly, speeds up employees serving customers, and makes it easier for owners to monitor business activities and allocate funds appropriately to procure new costumes.